Paradigma Keilmuan Dalam Pemikiran Pendidikan Islam Kontemporer Tantangan Dan Prospek - Muhammad AlFarobi; Rahmat Syukur; Latifah Addiba; Dewi Maya Sari (Qolamuna : Jurnal Studi Islam, 2022)
The development of creative and dynamic intellectual insights in light and integrated with Islam must be accelerated immediately. The old grudges that continue to be perpetuated and the culture's blind rejection of the West are not wise attitudes. This will only backfire on the intellectual development of Islam. This is where the "mental attitudes" of Muslim intellectuals need to be reviewed and reorganized. This attitude can be said to be quite moderate and quite acceptable among Muslims. Meanwhile, the main solution proposed by Tibi is secularization, which is the industrialization of a society which means the functional diffrensiation of its social structure and religious system. This solution seems to only open a front that confronts muslims in general. Secularity is not a realistic option when offered in Islam, so there are bound to be many challenges to it. Although Tibi is a reliable Muslim intellectual, accurate in photographing the problems faced by the world of Islamic education in general, but for solutions more colored by his daily religious attitudes, namely a Muslim who does not obey his religion. Keywords : Scientific paradigm, contemporary, prospect challenges